SCREENING FOR HYPOTHYROIDISM-RESULTS OF A STUDY CONDUCTED AT DISTRICT HEADQUARTER HOSPITAL, ABBOTTABAD - Gul, Nasreen; Farid, Jamila; Idris, Muhammad; Sarwar, Javed (Journal of Ayub Medical College Abbottabad, 2016)
Background: Sub-clinically hypo-functioning thyroid is a condition in which there is biochemical evidence of hypothyroidism but patient is clinically asymptomatic. This concept is not new. The typical picture of this condition is increased thyroid stimulating hormone and normal thyroxine levels. Subclinical hypothyroidism has been found to have variable prevalence ranging from 4-10% to 10-26%. Methods: This cross sectional study was conducted on 378 adult patients coming to outpatient department of District Headquarter Hospital Abbottabad over a period of two years from February 2013 to February 2015. Results: Out of the 378 individuals studied, 37 (9.78%) had subclinical hypothyroidism. Mean age of the patients was 43.5±10.5 years. Females outnumbered males, i.e., 24 out of 37 (65%). It was noted that there was no correlation between mean TSH level and gender or age of the patients. Conclusion: Subclinical hypothyroidism is not an uncommon condition and its diagnosis is established easily by doing thyroid hormone levels in fasting condition. Early diagnosis and therapeutic intervention may not only prevent the progression to clinical hypothyroidism but also help in preventing the wastage of resources on doing unnecessary investigations. Keywords: Subclinical hypothyroidism, Thyroid disorders, Pakistan